Assessing the Effects of Land Registration on Tenure Security in Kumasi, Ghana - , Christian Kofi Sarpong, Romanus Dokgubong Dinye, Christopher Kanpiim, Mark Owusu Yeboah (Archives of Current Research International, 2025)
In most developing nations, tenure insecurity is a chronic feature, especially in urban and peri-urban regions where land tenure is usually unrecorded, contentious, or dominated by pluralistic tenure regimes. In Ghana, the intersection of customary and statutory land tenure regimes has resulted in extensive land conflicts, failure to seek legal recognition, and negligible investment in land-related development. This paper evaluates the impact of land registration on tenure security in Kumasi. Employing an embedded case study design, the paper adopted a mixed quantitative and qualitative methodology, based on data collected through 383 land rights holders and interviews with land officers from the Lands Commission. The findings reveal that land registration is significant in guaranteeing tenure through the provision of legal proof, conflict minimization, and stimulating investment confidence. Over half of the respondents showed an improvement in legal security and a reduction in land conflicts, while ninety percent reported an increase in investment and productivity in land use after the registration process. The paper also reveals major barriers to registration, which include high costs, administrative inefficiencies, low awareness, and institutional inefficiencies. These barriers fall disproportionately on low-income groups and widen inequalities, especially targeting women and marginal groups. The paper concludes that while land registration holds the prospect of securing land rights and stimulating development, its success is highly dependent on complementary institutional reforms, inclusive policies, and public sensitization. Recommendations made are simplifying registration procedures, reducing costs, consolidating customary tenure within statutory systems, and enhancing transparency and accountability in land governance systems so that equitable access and tenure security can be extended to all.